How Gay, Bi, And Straight Male Students At Chulalongkorn University Use Facebook? - Smith , Boonchutima; Mahaarnuntaputt, Naruenun; Dangpheng, Tanaphon (2015)
The way in which people with different sexual orientations use certain types of media is an important topic of interest among communication scholars. Understanding the communication patterns in Facebook use among gay, bi, and straight people could shed light on differences in communication in this digital era. The objective of this study was to evaluate Facebook use among heterosexual and homosexual male students. Self-administered questionnaires were used to collect data from 400 undergraduate male students at Chulalongkorn University. Overall, male students were less actively engaged in conversations on Facebook compared to their female counterparts. Our results showed that approximately 1 out of 5 participants indicated that they liked to or used to have sex with men. Compared to straight men, gay and bisexual men are more active Facebook users. This group more frequently updated their status, commented on their friends' photos, posted photos and messages on their friends' pages, and showed support for others. We also found that gay and bisexual men gave advice to their friends on Facebook, as well as shared their personal problems. These results suggest that gay and bisexual men use Facebook to escape stress, entertain themselves, and cope with problems compared to straight men, who did not use Facebook to satisfy those needs and were found to be more reserved and less communicative.